The Creativity Indicators of Vocational Schools and Feasibility Analysis of Electrochemistry Module Based on Problem Based Learning Integrated on Battery Competence Unit - I Rohmi; M Masykuri; E Susilowati (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to analyze the feasibility of electrochemistry module based on Problem Based Learning (PBL) integrated on battery competence unit to improve students’ creativity of class X of Vocational High School. The electrochemistry module that developed was used indicator of creativity proposed by Piirto are 1) cognitive strategies macroabilities: a) clarifying issues, conclusions, or beliefs; b) analyzing or evaluating arguments, interpretations, beliefs, or theories; c) generating or assessing solution; and 2) cognitive strategies microskills: a) comparing and contrasting ideas, predictions, or interpretations; b) making plausible inferences, predictions, or interpretations; c) giving reason and evaluation evidence and alleged facts. The type of this study was a Research and Development (R & D) that used Borg and Gall’s development model. The module development stages were include: 1) research and information collecting, 2) planning, 3) develop preliminary form of product, 4) preliminary field testing, and 5) main product revision. The validation result by Aiken shows that V ≥ 0,75 indicates that the module is valid in content, presentation, language and graphic aspects. The results of teacher and students’ response questionnaires to the electrochemistry module in the preliminary field test stage show that the module can be categorized as very good.